The Efficacy of Lubiprostone in Patients of Constipation: An Updated Systematic Review and Meta‐Analysis - Umar Akram; Obaid Ur Rehman; Eeshal Fatima; Zain Ali Nadeem; Omer Usman; Waqas Rasheed; Ramsha Ali; Khawaja Abdul Rehman; Abdulqadir J. Nashwan (JGH Open)
ABSTRACT Background and Aim Lubiprostone increases chloride and water secretion in the intestines, and several studies have demonstrated the efficacy of lubiprostone in treating functional constipation. Several new clinical trials have emerged since the previous meta‐analysis conducted in 2020. We conducted this updated meta‐analysis to assess clinical efficacy of lubiprostone in these patients. Methods A systematic search was conducted on MEDLINE, Cochrane, and Scopus. Randomized controlled trials published between July 2019 and June 2024 were selected. Cochrane's RoB 2 tool was used to assess the risk of bias. A meta‐analysis was performed and findings were presented using forest plots. Results A total of 14 studies, comprising 4550 patients, were included in the review. Only 12 studies were pooled in the meta‐analysis. Lubiprostone was associated with greater spontaneous bowel movements (SBM) per week (RR 1.454, 95% CI 1.193–1.771) and SBM within 24 h (RR 1.790, 95% CI 1.491–2.150) in patients with chronic idiopathic constipation (CIC). However, it was not associated with abdominal pain in either arm (RR 1.415, 95% CI 0.873–2.294). In opioid‐induced constipation (OIC), lubiprostone increased SBM within 24 h (RR 1.277, 95% CI 1.105–1.475) but did not significantly affect abdominal pain (RR 4.321, 95% CI 0.624–29.941). Lubiprostone improved all selected SBM‐related and abdominal pain outcomes in patients with irritable bowel syndrome with constipation (IBS‐C). Conclusion Lubiprostone significantly improves all SBM‐related outcomes. Owing to its good safety and efficacy profile, lubiprostone can be used in the combination regimens for management of CIC, IBS‐C, and OIC.